Impacto dos custos de de transação decorrentes de estruturas de governança híbrida na gestão da cadeia de suprimentos: estudo de caso em uma indústria de construção naval - Pinheiro, Carlos David Pedrosa (2015)
The goal of supply chain is to deliver a set of value-added products or services from its source to the final consumer. The Supply Chain Management (SCM) SCM improves the performance of the individual companies and the supply chain as a whole. However, this improvement is Just possible due to an efficient flow of materials, information, and finances. The degree of implementation of SCM depends on the levels of cooperation among agents and the Transaction Cost Economics (TCE) provides a key building block to analyze the costs incurred due to certain choices of governance structures and allows you to direct actions to reduce them. Thus, the Transaction Cost Economics (TCE) is an economic theory that provides an analytical framework for investigating the governance structure of contractual relations within a supply chain. The goal of this study is to identify the impact of transaction costs present in hybrid structures of governance in managing the business supply chain participating in the naval industry of Ceará. Based on the analytical categories defined by the ECT, it was possible to develop constructs that allowed visualization of the nodal points between the ECT and the GCS. Starting from such nodal points, the survey assessed the level of importance and the current state of analytical categories in the yard vision and subcontractors of the metallurgical area and identified the main causes and mitigating actions transaction costs occurring in the relationship between the same agents . The study also looked at chain shipyard supplies compared with the ideas aspects of GCS. Finally, the survey found that improvements in institutional conditions trespass, necessarily, for an improvement of the contractual and are inexcusable increased exchange of information safeguards, the definition of a plan for the chain, investment in human capital agents and long-term relationships management with subcontractors of the metallurgical area